SURFACE CURRENT STUDY USING LARGE SCALE PARTICLE IMAGE VELOCIMETRY METHOD WITH VARIATIONS IN VIDEO RESOLUTION - Mutu Siregar, Andrean
The Large-Scale Particle Image Velocimetry (LSPIV) method is an image-based technique used to identify fluid flow. The aim of this study is to identify surface currents in the Bondet Estuary with a focus on testing drone video resolutions, which will then be verified using a current meter instrument and further analyzed. Current meter measurements showed that the maximum current speed at the estuary (Station 1) during high tide reached 0.45 m/s and 0.04 m/s during slack water. The current speed decreased significantly upstream (Station 11) with a range of 0.07-0.17 m/s during high tide and increased to 0.24 m/s during low tide. LSPIV analysis showed that the average current speed magnitude during high tide for 4k, 1080p, and 720p video resolutions was 0.303 m/s, 0.275 m/s, and 0.199 m/s respectively, with the direction towards upstream, while during low tide it was 0.15 m/s, 0.13 m/s, and 0.097 m/s with the direction towards downstream. Validation between current meter measurements and LSPIV estimations showed that the MAPE values for 4k, 1080p, and 720p resolutions were 3.28%, 9.03%, and 33.3% respectively. Pixel correlation at 4k resolution ranged from 0.7-0.8, whereas for 1080p and 720p resolutions, it was less than 0.6. Based on MAPE validation and pixel correlation results, LSPIV with 4k video resolution provided the most optimal results for surface current identification.